A Membrane-Bound NAD(P)(+)-Reducing Hydrogenase Provides Reduced Pyridine Nucleotides during Citrate Fermentation by Klebsiella pneumoniae - Steuber, Julia (American Society for Microbiology, 1999)
During anaerobic growth of Klebsiella pneumoniae on citrate, 9.4 mmol of H(2)/mol of citrate (4-kPa partial pressure) was formed at the end of growth besides acetate, formate, and CO(2). Upon addition of NiCl(2) (36 μM) to the growth medium, hydrogen formation increased about 36% to 14.8 mmol/mol of citrate (6 kPa), and the cell yield increased about 15%. Cells that had been harvested and washed under anoxic conditions exhibited an H(2)-dependent formation of NAD(P)H in vivo. The reduction of internal NAD(P)(+) was also achieved by the addition of formate. In crude extracts, the H(2):NAD(+) oxidoreductase activity was 0.13 μmol min(−1) mg(−1), and 76% of this activity was found in the washed membrane fraction. The highest specific activities of the membrane fraction were observed in 50 mM potassium phosphate, with 1.6 μmol of NADPH formed min(−1) mg(−1) at pH 7.0 and 1.7 μmol of NADH formed min(−1) mg(−1) at pH 9.5. In the presence of the protonophore carbonyl cyanide m-chlorophenylhydrazone and the Na(+)/H(+) antiporter monensin, the H(2)-dependent reduction of NAD(+) by membrane vesicles decreased only slightly (about 16%). The NADP(+)- or NAD(+)-reducing hydrogenases were solubilized from the membranes with the detergent lauryldimethylamine-N-oxide or Triton X-100. NAD(P)H formation with H(2) as electron donor, therefore, does not depend on an energized state of the membrane. It is proposed that hydrogen which is formed by K. pneumoniae during citrate fermentation is recaptured by a novel membrane-bound, oxygen-sensitive H(2):NAD(P)(+) oxidoreductase that provides reducing equivalents for the synthesis of cell material.